Integration of hepatitis B virus DNA in chromosome-specific satellite sequences. - Shaul, Y (1986)
We previously reported the cloning and detailed analysis of the integrated hepatitis B virus sequences in a human hepatoma cell line. We report here the integration of at least one of hepatitis B virus at human satellite DNA sequences. The majority of the cellular sequences identified by this satellite DNA were organized as a multimeric composition of a 0.6-kilobase EcoRI fragment. This clone hybridized in situ almost exclusively to the centromeric heterochromatin of chromosomes 1 and 16 and to a lower extent to chromosome 2 and to the heterochromatic region of the Y chromosome. The immediate flanking host sequence appeared as a hierarchy of repeating units which were almost identical to a previously reported human satellite III DNA sequence.